Impact of statutory audit and corporate taxation on profitability of selected listed companies in Nigeria - Grace Awotayo-Ayeni Oyinkansola; Cordelia Onyinyechi Omodero (Cogent Economics & Finance, 2023)
The study evaluates the impact of statutory audit and corporation tax charges on the profitability of Nigerian listed firms using data from 2016 to 2021. This study is highly inspired by corporate governance detects, which mandate corporations' stewardship, civic, and transparency duties to stakeholders. However, there is a need to analyze the compliance rate and its implications for corporate performance. The research data for this study are derived from the yearly financial reports of the sampled businesses. The descriptive statistics, correlation matrix, Hausman test, fixed and random effects techniques are also used in the study to determine the suitability of the data collected for the study and to determine the relationship between the study variables as well as the influence of the predictor variables on the reliant factors. According to the findings, corporate tax costs and statutory audit have a considerable impact on business profitability but while the corporate tax impact positively on profitability, an immaterial negative effect on net asset base is established. The total assets employed as the control variable in this study does not have tangible effect on both the profit after tax and net asset base. In terms of the relationship, all variables have a large and very strong positive interconnection with one another except the total assets applied as the moderating variable. It is also established that the data used in this inquiry is entirely normally distributed and appropriate for analysis. According to the findings, organizations should maintain a consistent statutory audit and regularly comply with tax obligations to establish a stronger corporate image that would promote excellent financial performance.
Keywords: 330; corporate tax; firms; net asset; profit after tax; Statutory audit